If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying Y + 8 = 2y + -4 Reorder the terms: 8 + Y = 2y + -4 Reorder the terms: 8 + Y = -4 + 2y Solving 8 + Y = -4 + 2y Solving for variable 'Y'. Move all terms containing Y to the left, all other terms to the right. Add '-8' to each side of the equation. 8 + -8 + Y = -4 + -8 + 2y Combine like terms: 8 + -8 = 0 0 + Y = -4 + -8 + 2y Y = -4 + -8 + 2y Combine like terms: -4 + -8 = -12 Y = -12 + 2y Simplifying Y = -12 + 2y
| -3x+10=94+4x | | 5y^2-7y=-2 | | 27=3(2x-7) | | -11x-400-.03x=840 | | 27=15+9 | | 3x-9=5x+2 | | -1.08=0.9v | | 2x+2y=2x+9 | | 4x^2-8x+4y^2+12y-131=0 | | 6s+2=-10 | | K-7+6= | | 12n-17n+6=32 | | v^2-4vx-12x^2=0 | | 3x(2)=12+5x | | 96=16+2x | | 9(t-6)+3=6(2t+3)-9 | | (17b-5)-4(4b+4)=-6 | | (X^2+4)=25 | | 2a+8a=8 | | (2x-4)-(5x+3)= | | 4c-43=7c-193 | | 44=4(x-5) | | -43=2+9x | | 3(y-7)=2(4+y) | | 4m=m+21 | | 20x^2-25+5= | | -2=4r-s | | 4(j-3)=23-3j | | 2x+5(x-18)=-174 | | 90=-8y+50 | | -5a+3=1 | | 2m=5m+60 |